Pentingnya Pengembangan Kelembagaan Pengelolaan Prasana Perkotaan Lintas Batas Administrasi Di Kawasan Metropolitan Bandung - Krismayati Tasrin (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2006)
Bandung Metropolitan Area is growing up quickly as result of conurbation process and sub urbanization phenemenon. A large urban are created when neighboring towns spread into and merge with each other. Bandung City and some municipalities arround it have a correlation between one and others. This is characterized by a regional cohesion in many aspects such as economy, social, cultural, etc. Today, public infrastucture is managed by each regional government who has autority in their own home and has no authority in their own home and has no autority to others region whereas public infrastructure is not restricted by administration border. By increasing the need of public services quality, each municipality has to have an integrated infrastructure management with others.